Academic Bargaining: Origins and Growth - Lacombe, Trefflé (Relations industrielles / Industrial Relations, 1978)
This article reviews "Academic Bargaining: Origins and Growth" by James P. Bégin, Theodore Settle and Paula Alexander.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z